Efektivitas Perubahan Lembaga Pendidikan Tenaga Kependidikan (LPTK)/Institut Keguruan dan Ilmu Pendidikan (IKIP) menjadi Universitas - Idris H.M Noor (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
The research investigates the effectiveness of the status change of teacher training institute into university. Research uses mixed quantitative and qualitative approach, evaluation and case study methods. sampling are stratified and purposive from eight public universities. Data collecting was Focus Group Discussion (FGD), kuessioner, and interview. Data analysis used percentage quantitative and case analysis of the unique of each study program at each university. The study shows: 1) universities are still keeping their roles as their core business to produce teachers and educational administrators, 2) Students competence significantly improves due to the education and non education program of the study reciprocally give or help each other as well as share their experience to enhance studentsâ€™ competence in science and social subjects, 3) the enrolement of students tends to be increased every year with high academic qualification candidates, 4) curriculum consists of education and non education (pure science and social subjects), 5) lectrurersâ€™ qualification also increases significantly, srata 1 tends to be decrease, while master dan doctor degree-S2/S3 increase significantly every year/period, 6) budget of each university and faculty is different due to the different location of universities and needs of each faculty, and 7) students cummulative achievement index (3.275) increases every year.ABSTRAKÂ Tujuan penelitian ini untuk mendapatkan informasi mengenai efektivitas perubahan status kelembagaan IKIP/LPTK ke universitas. Pendekatan yang digunakan, yaitu pendekatan kuantitatif dan kualitatif (mixed method) dengan metode evaluasi dan metode studi kasus. Sampel menggunakan stratified dan purposive sampling dari delapan universitas negeri. Pengumpulan data melalui Focus Group Discussion (FGD), wawancara, pengisian kuesioner. Analisis data menggunakan teknis kuantitatif dengan persentase dan analisis kasus melihat keunikan masing-masing prodi di masing-masing universitas. Hasil penelitian menunjukkan bahwa:1) universitas eks LPTK/ IKIP tetap menjalankan core bussines-nya sebagai produsen pendidik dan tenaga kependidikan, 2) peningkatan kompetensi keilmuan mahasiswa cukup efektif karena program studi pendidikan dan program studi murni saling mengisi satu sama lain, 3) peminat mahasiswa terus meningkat setiap tahunnya dengan calon mahasiswa yang berkualifikasi akademik tinggi, 4) menggunakan kurikulum pendidikan dan nonpendidikan, 5) kualifikasi dosen terus meningkat (pendidikan S1 terus berkurang, sedangkan S2 dan S3 terus bertambah), 6) biaya setiap universitas dan fakultas berbeda karena perbedaan tempat dan kebutuhan, dan 7) keluaran (ouput) lulusan mahasiswa memiliki IPK mencapai di atas rata-rata di atas 3.275.